Towards inclusive social protection program coverage in the Philippines: Examining gender disparities - Aubrey D. Tabuga; Carlos C. Cabaero (Philippine Institute for Development Studies (PIDS), 2019)
The Philippines, being prone to natural calamities and vulnerable to economic fluctuations, has much to accomplish in terms of improving its population's access to social protection. A focus on women's access is crucial in the light of their significantly lower labor force participation rate (LFPR) compared to men's and because many women are in the informal sector. A study by the Asian Development Bank noted that the disparities in the access to social protection between men and women are found largely in social insurance, attributed to low representation of women in the formal sector resulting in the inability of many women to gain social insurance benefits. Using survey-based data from the Philippine Statistics Authority, this paper examines people's access to social protection by looking at the coverage of various social protection programs such as the Government Service Insurance System for government workers, Social Security System for private sector workers, and PhilHealth. It examines the circumstances of different groups of workers such as wage and nonwage earners, the self-employed, and the household workers, among others. It identifies the types of occupations and locations of those without access to social protection who belong to the bottom 30 percent of households as these represent those most in need of government intervention. This analysis is supplemented by an empirical estimation of the likelihood to be covered by social insurance schemes for both employed and unemployed persons. It likewise offers a closer look at the characteristics of those not in the labor force because this is a primary reason for the exclusion of many individuals in accessing social protection. Furthermore, the study examines the social insurance aspect of the Pantawid Pamilyang Pilipino Program (4Ps). The overall goal of this undertaking is to recommend insights for purposes of improving the coverage of social protection programs in the country.
Keywords: 330; social protection; women; labor force participation; social insurance